THE CREATIVE INFLUENCE OF PABLO PICASSO ON THE WORKS OF LATVIAN ARTISTS - Apele, Diāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Pablo Picasso is one of the Western modern culture creators of the first part of the 20th century. Picasso has influenced numerous artists directly or indirectly – both the followers of Western school and artists here, in Latvia. The main topic of this research is Pablo Picasso's influence on Latvian artists, specifically – Visvaldis Ziediņš, Rūdolfs Pinnis and Aleksandrs Dembo. Picasso stands out for exceptionally virtuosic style – it was characteristic of him to begin each new work as an individual wholeness, experimenting with graphic forms, colours, textures, lines, volumes, playing with relations of dark and light and work's emotional atmosphere. Similarly, in the works of all three artists, the experiments with graphic forms and textures and virtuosic plays with relations of dark and lights and emotions are perceptible. Sharp sense of epoch, refined means of expression, depth of thinking, pictoriality, freedom of inspiration, nonconformity, intellectually difficult practice, lyrism, lightness and looseness, expressivity, spirituality – this is the common denominator of the artists – V. Ziediņš, R. Pinnis and A. Dembo. For all these prominent artists, Picasso’s creative work was not an object of imitation, but rather a launch pad to start acquiring the experience they were fascinated by. Research aim: to characterize creative work of the great Spanish artist Pablo Picasso and analyse his creative influence in the works of Latvian artists. Research methods: theoretical: the analysis of the study fields literature and internet resources.